Pembangunan Sistem Aplikasi Rekam Medis Elektronik Dan Pendaftaran Pasien Online Berbasis Web (Studi Kasus : Klinik Medis Elisa Malang) - Clara Pusparani; Bayu Priyambadha; Achmad Arwan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Management information is the main thing that has to be met by companies with a large and complex data. Currently, many hospitals, clinics, health centers, as well as the practices of doctors have used information system to facilitate data management and improve the quality of service to patients.But Klinik Elisa Malang encountered obstacles in registration of patients and medical record search.One patient could take 5-15 minutes to perform the registration process, including the search of the patient's medical record or creating medical record documents for new patients.This process can take much longer if a patient's medical record document was not found or is found in the broken state, the officer should make a new medical record. Based on these problems, the authors developed the electronic medical record system and online patient registration web-based that provides medical registration for old patients and also has features that are related to the patient's medical record management that have been converted to electronic form.The author uses the software development life cycle with waterfall model. Testing is done using unit testing with whitebox method and validation testing using blackbox method that produces valid values on all test cases, and compatibility test with 82% valid results.